How natural capital accounting frameworks fail ecosystem services - Hugo Jachmann; John E. Scanlon; Sarah M. W. Maston (European Journal of Environmental Sciences)
The United Nations (UN) System of Environmental-Economic Accounting – Ecosystem Accounting (SEEA – EA, UN 2021) has the potential to provide decision-makers with valuable information about the economic value of ecosystems and their components. However, the system has several shortcomings that must be addressed. The need for hard data, the focus on economic value over ecological value and integrity, the reliance on monetary valuation and the lack of clear guidance on the integration of the monetary values into decision-making processes and policies, are some of the issues that must be addressed for the framework to be an effective tool for promoting sustainable management of ecosystems. This is especially important because the ultimate goal of this exercise is to mitigate climate change and to protect biodiversity; to maintain a liveable planet for future generations by focusing on the valuation and accounting for ecosystem services provided by natural capital. Options to improve the system, as well as an alternative model, are briefly discussed. However, our fear is that the system in use is rapidly becoming too academic, too complicated, too time consuming and too easy to be controlled by some in the financial sector. The protection and restoration of ecosystems should not depend on highly complicated bookkeeping systems that may take some more years to finalize and many years to implement, but it does require urgent and collective action to reduce emissions and put a halt to ecosystem degradation, biodiversity loss and climate change – namely a collective change in attitudes and a complete revision of existing economic theories.